Analisis Konsumsi dan Tabungan Masyarakat di Indonesia - Engla Desnim Silvia; Rina Susanti (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2019)
The purpose of this study to identify and analyze: (1) consumption of the previous period, the current period disposable income and disposable income previous period on the level of consumption in Indonesia, (2) the current period disposable income, disposable income of the previous period, the consumption of the current period, consumption and interest rates on saving the current period in Indonesia.The result showed: (1) there isi a significant effect between the consumption of the previous period, disposable income of the current period and disposable income together the level of consumption in Indonesia, (2) there is a significant effect between the current period disposable income, disposable income of the previous period, the current period consumption, the consumption of the previous period and current periode interest together to word saving in Indonesia